2013
DOI: 10.1002/ptr.4951
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Beetroot Juice on DMBA‐induced Damage in Liver and Mammary Gland of Female Sprague–Dawley Rats

Abstract: quinone oxidoreductase-1. In mammary gland, beetroot juice induced the level of glutathione S-transferase pi, enzyme involved in active metabolites of DMBA detoxification. The final effects of beetroot juice are tissue specific and depend on the class of carcinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 38 publications
0
26
0
1
Order By: Relevance
“…Beetroot extracts were proven to be efficient in vitro inducers of quinone reductase, another family of phase II detoxification enzymes . In the study of Szaefer et al , beetroot juice treatment increased GST levels in mammary glands and induced GST activity in the hepatic cells of female Sprague‐Dawley rats treated with 7,12‐dimethylbenz[ α ]anthracene (DMBA). Betalains from beetroot juice also exhibited a protective role in N ‐nitrosodiethylamine‐induced liver injury in Wistar rats through phase II enzyme induction …”
Section: Resultsmentioning
confidence: 99%
“…Beetroot extracts were proven to be efficient in vitro inducers of quinone reductase, another family of phase II detoxification enzymes . In the study of Szaefer et al , beetroot juice treatment increased GST levels in mammary glands and induced GST activity in the hepatic cells of female Sprague‐Dawley rats treated with 7,12‐dimethylbenz[ α ]anthracene (DMBA). Betalains from beetroot juice also exhibited a protective role in N ‐nitrosodiethylamine‐induced liver injury in Wistar rats through phase II enzyme induction …”
Section: Resultsmentioning
confidence: 99%
“…Hepatoprotective effect was suggested through induction of phase II enzyme quinone reductase by betalain‐rich red beet extract (Wettasinghe and others ), particularly betanin (Lee and others ). Feeding trials involving rats showed that betalain‐rich red beet juice mitigated hepatic toxicity caused by N ‐nitrosodiethylamine (NDEA), carbon tetrachloride (Kujawska and others ), and 7,12‐dimethylbenz(a)anthracene (DMBA) as a result of improved antioxidant status and enhanced expression of phase II enzyme quinone reductase (Szaefer and others ). Liver toxicity was efficiently offset by the protective effects of betanin, such as reinstating cytochrome P450 enzyme expression elevated by toxicant treatment, improvement in liver redox status, and restoration of mitochondrial functions (Han and others ,b).…”
Section: Dietary Safetymentioning
confidence: 99%
“…The most potent antioxidant molecules in BTJ are thought to be the betalain pigments, which are responsible for beetroot’s violet colour [28]. The betalains, and betanin in particular, are very effective electron donors that have been shown to not only attenuate ROS mediated injury but also to upregulate endogenous antioxidant enzymes and stimulate host defence [29,30,31,32]. In addition, BTJ is rich in nitrate, which, via its reduction to nitric oxide (NO) might have indirect antioxidant effects by supressing the accumulation of leukocytes [33], which are thought to be the main producers of ROS after muscle-damaging exercise [34].…”
Section: Introductionmentioning
confidence: 99%